Development and validation of a taqman multiplex pcr assay for the gene dosage quantification in cancer (2012)
Gene dosage tests are very important for the molecular diagnosis of diseases caused by either deletion or amplification of a specific DNA region containing certain genes. Changes in gene copy number may lead to under- or over expression of genes responsible for the disease phenotype. Discovering these defects and understanding their biological meaning can lead to improved therapeutic opportunities in cancer. Fluorescent in situ hybridization (FISH) still remains the gold standard method for gene dosage analysis. However have several limitations since locus specific probes are expensive, the procedure is significantly time-consuming and tandem microduplications may be undetected as a result of the limited resolution on metaphase spreads. Quantitative Real-time PCR is a rapid assay with results available in 24h, has advantages in terms of sensitivity and specificity. In the present study, we have developed an assay using TaqManTM multiplex Real-time PCR for gene dosage analysis of oncogenes EGFR, ERBB2, AKT2, CMYC, MYCN, MYCL1, PI3KCA and REL in human cell lines. This method calculates the copy number of each oncogen and is a promising alternative technique to FISH and Southern blot. Therefore, this technique could be considered as a powerful method gene dosage quantitation in clinical and research genetic surveys.